Perbandingan Pertumbuhan Jumlah Mata Tunas Bibit Bagal Tebu (Saccharum officinarum L.) Varietas GMP2 dan GMP3 - Wantia Oktami; Wiwik Indrawati; Abdul Azis (Politeknik Negeri Lampung, 2016)
The aim of this research is to analyse the effect of the number of buds per stem cutting on vegetative growth, especially from germination phase to budding phase of sugarcane GMP2 and GMP3 varieties. Research carried out in the garden practices of The State Polytechnic of Lampung, Rajabasa, Bandar Lampung in November 2014 to February 2015. The research method used a factorial randomized block design, consisting of two factors. The first factor was the sugarcane varieties, i.e. GMP2 and GMP3. The second factor was the amount of buds from stem cutting which consists of 4 levels: 1, 2, 3, and 4 buds per stem cutting. Based on the results of this research there was no interaction between variety and number of buds from stem cutting. Varieties affected on plant height, number of leaves, number of tillers, length of roots shoots (butters roots) and roots length rope (rope system roots). While the number of buds seeds mule had no effect on plant height, number of tillers, stem diameter, length of roots surface (superficial roots), and heavy roots.Keywords: number of buds, stem cutting, sugarcane varietiesPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/33